PENGARUH MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN DIMEDIASI KEPUASAN KERJA - Fian Ardiaz (Jurnal Bisnis dan Manajemen, 2017)
The purpose of this study was to determine the influence of motivation and transformational leadership style on employee performance mediated job satisfaction in PT Bank Rakyat Indonesia Malang Kanca Marthadinata. This study uses research data in the form of a questionnaire. The number of samples in this study were 87 employees working at PT. Bank Rakyat Indonesia Malang Kanca Marthadinata. The sampling technique used in this study in saturated sampling. Analysis of the data used in this study were Path Analyze using SPSS software. The result of this study indicate that (1) Motivation influential work in a positive and significant impact on the performance of employees (2) work motivation influence positively and significantly related to job satisfaction (3) The leadership style transformational positive and significant effect on the performance of employees (4) Transformational leadership positive and significant impact on job satisfaction (5) job satisfaction positive and significant effect on the performance of employees (6) Motivation indirect effect and significant to employees performance mediated job satisfaction (7) Transformational leadership indirect effect and significant to the performance mediated employee job satisfaction DOI : https://doi.org/10.26905/jbm.v4i1.1713